2023
DOI: 10.1002/adma.202212111
|View full text |Cite
|
Sign up to set email alerts
|

Phase‐Changeable Dynamic Conformal Electrode/electrolyte Interlayer enabling Pressure‐Independent Solid‐State Lithium Metal Batteries

Abstract: Lithium‐metal‐based solid‐state batteries (Li‐SSBs) are one of the most promising energy storage devices due to their high energy densities. However, under insufficient pressure constraints ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…In comparison to the reported configuration of SPEs-based ASSLMBs in Figure a, b, Table S5, Supporting Information, the electrochemical performance of ASSLMBs utilizing PLS1 electrolytes in our study is at the forefront, presenting a promising avenue for practical PEO-based ASSLMBs. , Specifically, the Li effect of the Li dendrites is utilized to fill the SbF 3 nanoparticles into the solid electrolyte to phagocytic and anchor the Li dendrites while completing the transformation of the stable SEI layer . It has been observed that SbF 3 nanoparticles can undergo lithiation with the neighboring Li dendrites, which possess a robust electron transport capability .…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…In comparison to the reported configuration of SPEs-based ASSLMBs in Figure a, b, Table S5, Supporting Information, the electrochemical performance of ASSLMBs utilizing PLS1 electrolytes in our study is at the forefront, presenting a promising avenue for practical PEO-based ASSLMBs. , Specifically, the Li effect of the Li dendrites is utilized to fill the SbF 3 nanoparticles into the solid electrolyte to phagocytic and anchor the Li dendrites while completing the transformation of the stable SEI layer . It has been observed that SbF 3 nanoparticles can undergo lithiation with the neighboring Li dendrites, which possess a robust electron transport capability .…”
Section: Resultsmentioning
confidence: 68%
“…Electrochemical performance comparison with the literature. , (a) Li–Li symmetric cells cycle time at 0.1 mA cm –2 and (b) the energy density of the full cells and the corresponding C-rate (1C ≈ 170 mA g –1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S2, LFP exhibits two peaks in the O 1s spectrum. One peak located at a high binding energy of around 531.5 eV relates to −PO 4 and hydroxyl groups on the surface of LFP, while another one at a lower binding energy of about 529.5 eV is attributed to lattice O of LFP. ,, Notably, the peak at 529.5 eV disappeared in the O 1s spectrum of F-LFP-LGD, F-LFP-MGD, and F-LFP-HGD in Figure S2. Meanwhile, new peaks associated with C–O (533.5 eV) and Si–O (532.6 eV) originating from the grafted KH570 are observed, further confirming the hydrolysis reaction between KH570 and LFP. , Furthermore, the ratio of the peak density of Si–O progressively increases with increasing reaction time, suggesting that surface chemistry altered from hydroxyl groups to targeted CC groups in varying degrees, leading to gradient distribution of functional groups on the surface of the cathode.…”
Section: Resultsmentioning
confidence: 99%
“…One peak located at a high binding energy of around 531.5 eV relates to −PO 4 and hydroxyl groups on the surface of LFP, while another one at a lower binding energy of about 529.5 eV is attributed to lattice O of LFP. 34,36,37 Notably, the peak at 529.5 eV disappeared in the O 1s spectrum of F-LFP-LGD, F-LFP-MGD, and F-LFP-HGD in Figure S2. Meanwhile, new peaks associated with C−O (533.5 eV) and Si−O (532.6 eV) originating from the grafted KH570 are observed, further confirming the hydrolysis reaction between KH570 and LFP.…”
Section: Construction Of Functionalized Lfp With Differentmentioning
confidence: 99%
“…[64][65][66][67] Quasi-solid polymer electrolytes prepared by in situ polymerization can obtain conformal interface contacts, thus reducing the interfacial resistance and realizing rapid charge transfer at interfaces. 68 Ciucci and coworkers prepared a flexible and highly conductive DOLbased quasi-solid polymer electrolyte, obtaining an integrated battery structure and outstanding ionic conductivity of 1 mS cm À1 @À30 1C. 39 The formed polymer-dominated SEI provided rapid Li + transport and superior interfacial stability by inhibiting parasitic reactions between the MP and the Li metal anode.…”
Section: Low-temperature Breakthroughsmentioning
confidence: 99%